Differentials in Men’s Participation in Family Planning in Tanzania: A Case Study of Mbeya Region - Sichona, Francis; Mbago, Maurice (Tanzania Journal for Population studies and Development, 2008)
This paper investigates factors influencing men’s participation in family planning in Mbeya Region, Tanzania. Mbeya was selected for this study because it is one of the regions with high fertility and low contraceptive use in the country. Using field data collected from 568 married men aged between 15 and 59 years, the paper shows that men’s knowledge of contraceptives in Mbeya region was highest for male condoms and lowest for the diaphragm. The study also found that men’s current use of modern contraceptives is significantly associated with age, education, number of living children, and desired number of additional children. However, when the effect of these variables was tested through a logistic regression, only education and number of living children were found to be significant predictors of current use of modern contraceptives.